Robotic and open partial nephrectomy for tumors in a solitary kidney. (September 2020) - Abedali, Zain A; Monn, M Francesca; Cleveland, Brent E; Sulek, Jay; Bahler, Clinton D; Koch, Michael O; Bihrle, Richard; Masterson, Timothy A; Gardner, Thomas A; Boris, Ronald S; Sundaram, Chandru P
Introduction and objective: Traditionally, patients with renal masses in solitary kidneys were managed with an open partial nephrectomy. With improving techniques, robotic-assisted partial nephrectomy in the setting of a solitary kidney is increasingly utilized. The objective of this study was to compare open partial nephrectomy and robotic-assisted partial nephrectomy outcomes in solitary kidney patients. Methods: A retrospective study of 536 total patients who underwent partial nephrectomy between 2004–2016 was performed. Of these patients, 23 had a renal mass in a solitary kidney. Patient demographics, perioperative values, and surgical outcomes were analyzed using descriptive statistics to compare open partial nephrectomy to robotic-assisted partial nephrectomy. Results: Of the 23 patients in the cohort, 52% ( n =12) underwent open partial nephrectomy and 48% ( n =11) underwent robotic-assisted partial nephrectomy. Patient characteristics were not significantly different. The mean (standard deviation) nephrometry score was 6.9 (1.8) for open partial nephrectomy and 6.1 (1.9) for robotic-assisted partial nephrectomy ( p =0.290). The mean (standard deviation) pre-operative creatinine was 1.2 (0.3) in open partial nephrectomy and 1.5 (0.4) in robotic-assisted partial nephrectomy, which did not reach statistical significance ( p =0.110). No difference in postoperative kidney function, Clavien grade 3 or higher complication rate, blood loss, or hospitalization length was noted. Conclusion: Although traditionally patients with a tumor in a solitary kidney are counseled to undergo open partial nephrectomy, robotic-assisted partial nephrectomy is a safe alternative with no decrease in postoperative renal function when compared with a similar cohort of patients undergoing open partial nephrectomy in a solitary kidney. Level of evidence: Level II